Relation between exercise central haemodynamic response and resting cardiac structure and function in young healthy men. (30th October 2015) - Babcock, Matthew C.; Lefferts, Wesley K.; Heffernan, Kevin S.
Summary: Background: Left ventricular (LV) structure and function are predictors of cardiovascular (CV) morbidity and mortality and are related to resting peripheral haemodynamic load in older adults. The central haemodynamic response to exercise may reveal associations with LV structure and function not detected by traditional peripheral (brachial) measures in a younger population. Purpose: To examine correlations between acute exercise‐induced changes in central artery stiffness and wave reflections and measures of resting LV structure and function. Methods: Sixteen healthy men (age 26 ± 6 year; BMI 25·3 ± 2·7 kg m −2 ) had measures of central haemodynamic load measured before/after a 30‐s Wingate anaerobic test (WAT). Common carotid artery stiffness and reflected wave intensity were assessed via wave intensity analysis as a regional pulse wave velocity (PWV) and negative area (NA), respectively. Resting LV structure (LV mass) and function [midwall fractional shortening (mFS)] were assessed using M‐mode echocardiography in the parasternal short‐axis view. Results: There was a significant association between mFS and WAT‐mediated change in carotid systolic BP ( r = −0·57, P = 0·011), logNA ( r = −0·58, P = 0·009) and PWV ( r = −0·44, P = 0·045). There were no significant associations between resting mFS and changes in brachial systolic BP ( r = −0·26, P >0·05). There were no associations between resting LV mass and changes in any haemodynamic variable ( P >0·05). Conclusion: Exercise‐induced increases in central haemodynamic load reveal associations with lower resting LV function in young healthy men undetected by traditional peripheral haemodynamics.